The Role of Mediators in Minimizing Divorce Rates at the Jepara Religious Court (PERMA Juridical Review Number 1 of 2016) - Sigit Noor Rohman; Fatkiyatus Su’adah; Tiara Yuliarsih (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
The Religious Court of Jepara has carried out mediation in accordance with Supreme Court Regulation (PERMA) No. 1 of 2016, which is designed as an alternative dispute resolution mechanism before a case proceeds to judgment. Nevertheless, the practice of mediation in 2022–2023 has not achieved the expected outcomes, as the success rate remains relatively low and cannot yet be regarded as effective. This study aims to examine two key issues: the factors that contribute to both the success and failure of mediation, including the obstacles encountered during the process, and the efforts of mediators to minimize the divorce rate in the Jepara Religious Court. The research applies a field research approach by collecting data from legal literature, such as books and journals, combined with interviews, while the analysis employs an inductive method, moving from empirical findings to theoretical explanations, to avoid data manipulation. The results show that mediation has been implemented in line with PERMA No. 1 of 2016, but the effectiveness is limited because many disputing parties lack genuine intentions to reconcile. Emotional factors and unwillingness to repair the relationship are the main barriers. Mediators attempt to reduce divorce by demonstrating seriousness, empathy, and persuasive communication strategies, encouraging parties to reconsider their decision to separate.